The Role of Organizational Citizenship Behavior (OCB) as a Mediation in the Influence Of Organizational Competence and Culture on Employee Performance - Bastotan, Rosid; Achmad, Nur (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
Strong and knowledgeable human resources may ensure product quality and service levels while also boosting corporate performance and progress. The goal of this research was to quantify the influence of an organization's competency and culture in increasing employee performance, as seen through organizational citizenship behavior or OCB as mediation, and a total of 76 respondents from PT. San Makmur Garment used Smart PLS as using partial least square. As a result, it concludes that competency has no major impact on employee performance but can be impact as such when mediated by OCB. On the other hand, organizational culture can have a major impact on employee performance, but when mediated by OCB, the results are negative or insignificant.